MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN KURIKULUM 2013 MELALUI PEMBIMBINGAN DAN PELATIHAN PROFESIONAL OLEH PENGAWAS SEKOLAH DI SMK GALUNGGUNG KOTA TASIKMALAYA TAHUN 2016 - Usep Saepudin (Universitas Galuh, 2019)
The method used in this research is descriptive method, using percentage techniques to see the increase that occurs from cycle to cycle. In the implementation of the first cycle of action seen the teachers are still learning to understand in the preparation of the 2013 Curriculum RPP. This can be seen from the acquisition of scores Yeri Maesuri, S.Pd scored 57.50%, Subhanulfalah, ST scored 55.00%, Tessa. W, ST got a score of 52.50% and Eman Sulaeman, S.Pd got a score of 52.50%. The evaluation results in the first cycle reached an average of 54.34%. This means that the teachers are still in the learning process in understanding and making the 2013 curriculum lesson plan. In the implementation of the second cycle, the teachers already understood the preparation of the 2013 curriculum curriculum. This can be seen from the scores obtained by Yeri Maesuri, S.Pd in the first cycle. the score was 57.50% and in the second cycle the score was 85.00%, Subhanulfalah, ST in the first cycle got a score of 55.00% and in the second cycle the score was 87.50%, Tessa W, ST in the first cycle got a score of 52.50% and in the second cycle the score was 82.50%, Eman Sulaeman, S.Pd in the first cycle the score was 52.50% and in the second cycle the score was 85.00%. The evaluation results in the second cycle reached an average of 85.00%. While the first cycle averaged 54.34%. This means that there is an increase of 30.66%. This shows that through professional guidance and training, teacher competence in the preparation of the 2013 curriculum curriculum is increasing.